Translation of complex clauses in hemingway’s the old man and the sea from English into Arabic - Hamood, Muhammed Ibrahim (2019)
This study sought to investigate the translation of complex clause structure in the English novel “The Old Man and The Sea” and its Arabic rendering by Ali Al- Kasimi. The specific objectives of the study are: 1) To examine the extent to which the English nominal beta clause functionsin Hemingway’s “The Old Man and The Sea” have been preservedin the Arabic translation by Ali Al- Kasimi; 2) To find out whether the English adverbial beta clausefunctions in Hemingway’s “The Old Man and The Sea” have been retained in the identified Arabic translation; 3) To determine whether the translation of the ST complex clause structure into Arabic has applied Newmark’s theory of semantic or communicative translation; 4) To examine to what extent the rendered English nominal beta and adverbial beta clauses in the novel in Arabic has affected their intended meaning in the source text.The novelty of this study is in its focus on the translation of the English complex clause structure, which functions as a subject, an object and complement, into Arabic. Functional Grammar and Newmark’s theory of semantic and communicative translation underlie this study. A qualitative, descriptive research approach was employed in both data collection and analysis. The data comprised 103 complex clauses extracted from “The Old Man and The Sea” by Hemingway and their Arabic translations by Ali Al- Kasimi. The bilingual corpus was compiled according to certain criteria, in line with the objectives of the study. The data were analysed according to Halliday’s Functional Grammar and Newmark’s theory of semantic and communicative translation. The findings of the study revealed that in general, the complex clauses were translated into group, clause or complex clauses, which display different functions and loss of the intended meaning of the selected texts. These suggest difficulties in finding translation equivalence in the two languages, due to the nature of the English complex clause structure as well as Arabic. However, the study concludes that such difficulties could be overcome, in that a translator must determine the structure and function of each beta clause in the source and target texts and its influence on the quality of the message of the target text. In this manner, the translator would be able to find an accurate equivalent in Arabic without adding or deleting some linguistic items or particles. Finally, knowing the complex clause structure of the source language may assist translators to know of any change in or loss of meaning of the complex clause or its equivalence during the process of translation, for this has significant implications on the aesthetics value of the translated text, on the whole.